2007
DOI: 10.1002/chem.200700549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DNA‐Binding, Cleavage, and Cytotoxic Activity of New 1,7‐Dioxa‐4,10‐diazacyclododecane Artificial Receptors Containing Bisguanidinoethyl or Diaminoethyl Double Side Arms

Abstract: Novel 1,7-dioxa-4,10-diazacyclododecane artificial receptors with two pendant aminoethyl (3) or guanidinoethyl (4) side arms have been synthesized. Spectroscopy, including fluorescence and CD spectroscopy, of the interactions of 3, 4, and their copper(II) complexes with calf thymus DNA indicated that the DNA binding affinity of these compounds follows the order Cu(2+)-4>Cu(2+)-3>4>3, and the binding constants of Cu(2+)-3 are Cu(2+)-4 are 7.2x10(4) and 8.7x10(4) M(-1), respectively. Assessment by agarose gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 132 publications
1
69
2
Order By: Relevance
“…Interestingly the obtained hydrolysis rate enhancement by complex 1 shows very high nuclease activity. The pseudo Michaelis-Menten kinetic parameters k cat and K M for artificial nucleases for DNA cleavage that produced an enhancement rate of 10 6 -fold greater than the non-catalyzed ds DNA cleavage are collected in Table 3 These data reveal that the reported values of k cat and K M for different metal ions and metal complexes range from 40 to 0.04 h À1 and from 3.9 Â 10 À6 to 1.3 Â 10 À3 M, respectively [21,[36][37][38]41,[50][51][52][53][54][55][56][57][58][59]. Inspection of the available literature data for DNA cleavage by metal ions and by metal complexes clearly shows that complex 1 is considered to be one of the most efficient artificial nuclease for DNA cleavage; third most efficient catalyst.…”
Section: Kinetics Of Plasmid Dna Cleavagementioning
confidence: 99%
“…Interestingly the obtained hydrolysis rate enhancement by complex 1 shows very high nuclease activity. The pseudo Michaelis-Menten kinetic parameters k cat and K M for artificial nucleases for DNA cleavage that produced an enhancement rate of 10 6 -fold greater than the non-catalyzed ds DNA cleavage are collected in Table 3 These data reveal that the reported values of k cat and K M for different metal ions and metal complexes range from 40 to 0.04 h À1 and from 3.9 Â 10 À6 to 1.3 Â 10 À3 M, respectively [21,[36][37][38]41,[50][51][52][53][54][55][56][57][58][59]. Inspection of the available literature data for DNA cleavage by metal ions and by metal complexes clearly shows that complex 1 is considered to be one of the most efficient artificial nuclease for DNA cleavage; third most efficient catalyst.…”
Section: Kinetics Of Plasmid Dna Cleavagementioning
confidence: 99%
“…Our research group [29] Spectroscopic measurement showed that they hydrolyze the phosphodiester bond of DNA via "bifunctional cooperative catalysis", similar to SNase. In the first place, one guanidinium identifies and binds the phosphodiester bond in DNA by hydrogen bonding and electrostatic interaction, and helps the Cu(Ⅱ) center to bind the phosphodiester bond better (A).…”
Section: Bifunctional Cooperative Catalysismentioning
confidence: 99%
“…Although lanthanide metal ion complexes can catalyse the hydrolytic cleavage of nucleic acids effectively, they have the disadvantage that these metal ions are not bio-elements per se, therefore, such systems are cytotoxic, and can be used only in vitro [7]. Many studies have been reported that the phosphate diester bond can be cleaved by many transition metal ions complexes via the hydrolytic pathway [22,37 -41], such as those of Cu(II) [40,41], and Zn(II) [22,38,39]. In general, the Lewis acidities of binuclear metal complexes are stronger than those of mononuclear metal complexes, so the binuclear metal complexes can activate nucleophilic species, promote the departure of the leaving group, and stabilise the transition-state intermediate via the synergistic effect of the bimetal centre effectively.…”
Section: Multinuclear Metal Complexes Of Aza-crown Ethers Used As Mimmentioning
confidence: 99%